Sayyed Hossein Nasr (Sufisme Masyarakat Modern) - Annur, Barsihannor (Al-Hikmah, 2014)
Sayyed Hossein Nasr is one of the Muslem intellectuals who had been grown up in two condition, Islam classic and western. This condition had made the accumulations of his intellectual and integraty. In other side, intellectual as the effect of western educations had contributed to the values of his life. Nasr argued that human life must be based on the balance principle such as the balance of fulfilling bodily and spiritual needs. The true beattitude could not be fulfilled simply by bodily needs and conversely. Facing the globalization era, the Sufism offered which will not make any sense by offering the classical Sufism tradition. The values must be developed, adapted, reformulated, or reconstructed in current time. But it is still based on Sufism elements of humanity and transcendental. Sufisme is in esoteric dimension and the spiritual Islam tradition is expected to be particularly compatible and relevant to anyone who is in imperishable.